Ethno-medicinal uses and cultural importance of stingless bees and their hive products in several ethnic communities of Bhutan - Thubten Gyeltshen; Chet P. Bhatta; Tulsi Gurung; Pelden Dorji; Jigme Tenzin (BMC, 2024)
Abstract Background Indigenous and non-indigenous people in subtropical and temperate areas of Bhutan share an intricate relationship with stingless bees for diverse purposes including ethno-medicinal uses. Stingless bees hold significant importance in the realms of social, economic, cultural, and spiritual aspects. Bhutan's cultural traditions demonstrate a strong bond with the environment, exemplified by the regular use of honey from stingless bees for remedies such as treating the common cold, cough, and sore throat. Methods Ethnographic research was conducted to document the ethno-medicinal uses and cultural importance of stingless bees in Bhutan. We deployed semi-structured interviews with stingless beekeepers and honey collectors including traditional healers who perform religious rituals for curing and preventing physical and mental illness. Results We documented 22 different uses of stingless bee honey in food, medicine, veterinary medicine, crafts, beliefs, and religious purposes. The relative cultural importance (RCI) of stingless bees among Bhutan's ethnic communities was assessed through our calculations. It was determined that these bees hold notably greater significance for the Lhotshampa communities compared to other ethnic groups in Bhutan. This finding demonstrates the dependence of Hindu ethnic communities on natural resources in their everyday life. All participant communities largely exploit these bees through destructive extraction practices. They often find the natural nests in nearby forests, transfer them as a log hive to their backyards, and practice traditional meliponiculture. Conclusion The ethnic communities of Bhutan use stingless bees for various purposes and the local knowledge are persistent. However, significant efforts should be made to address the ethno-medicinal, ecological, biological, and commercial perspectives of meliponiculture in Bhutan.